Screening Indigenous Australia: Space, Place and Media in Frances Calvert’s Talking Broken - Peter Kilroy (Ilha do Desterro)
Drawing on the fields of postcolonial studies and media theory, this article analyzes Frances Calvert’s 1990 documentary, Talking Broken, which, inter alia, looks at the role of space, place and media amongst Australia’s ‘other’ Indigenous minority, Torres Strait Islanders. The article explores the historical and geographical complexity of the space-place-media relation (particularly in terms of the centre-periphery relations between the Torres Strait and the Australian mainland), and considers the extent to which Calvert – after the Australian bicentenary of 1988 – is able to absorb and playfully challenge such formulations. More broadly, it considers the extent to which contemporary Indigenous media might go further and enact a shift from absorbing and challenging such formulations to taking control of media institutions themselves.